Opioid Prescribing Patterns for Low Back Pain Among Commercially Insured Children. (1st September 2019) - Azad, Tej D; Harries, Michael D; Vail, Daniel; Zhang, Yi Jonathan; Ratliff, John K
Abstract: INTRODUCTION: Low back pain (LBP) may affect up to 20% of the pediatric population. No specific guidelines exist regarding pharmacotherapy for acute LBP in the pediatric population. Given this observation and the lack of data available regarding pharmacotherapy for pediatric LBP, we sought to characterize patterns of opioid prescribing in the pediatric population. METHODS: We used a national database to identify pediatric patients (age 5-17) with newly diagnosed with LBP between 2008 and 2015 who did not have a red flag diagnosis, had not received an opioid prescription in the 6 mo prior to diagnosis, and had 12-mo of continuous enrollment after diagnosis. We used logistic regression to model the association between sex, geographic region, categorical age, and our primary outcome, receipt of an opioid prescription in the year following diagnosis. RESULTS: Our sample included 268 228 opioid-naïve pediatric patients diagnosed with LBP between 2008 and 2015. We observed that 47 631 (17.8%) patients received physical therapy, 29 903 (11.2%) patients received chiropractic manipulative therapy, 658 (0.25%) patients received epidural steroid injection, and 281 (0.10%) patients received surgery. A total of 35 274 (13.2%) pediatric LBP patients were prescribed opioids within 12 mo from their diagnosis. Opioid prescribing decreased in all age groups over the study period age group 5 to 9 decreased from 4.2% to 2.7%, age group 10 to 14 decreased from 10.3% to 7.7%, and age group 15 to 18 yr decreased from 20.9% to 17.1%. Female pediatric patients were more likely than male patients to receive an opioid prescription (OR, 1.12, P < .0001). Patients ages 10 to 14 (OR, 2.89, P < .0001) and 15 to 18 (OR, 6.98, P < .0001) were significantly more likely to be prescribed opioids compared to patients in the youngest age group. CONCLUSION: To our knowledge, we report the first observational cohort study of opioids and LBP in the pediatric population. Our findings indicate that opioids are being used for newly diagnosed LBP and receipt of opioids are associated with patient demographic factors.